Mineralocorticoid receptor antagonists in the treatment of patients with chronic heart failure. Positions in 2015 - Yu F Osmolovskaya; I V Zhirov; S N Tereshchenko (Терапевтический архив, 2015)
Mineralocorticoid receptor antagonists (MCRA) are part of standard medical therapy for heart failure (HF). The clinical efficacy of MCRA in patients with systolic HF has been proven by randomized clinical trials. The efficacy of this drug group in patients with chronic HF with preserved left ventricular systolic function and the advent and practical introductions of safer new-generation MCRA remain to be answered.